Legal Responses to Domestic Violence in Marriages and Their Implication for Marriage Sustainability in Nigeria (Strathmore Law Journal, 2023)
Domestic violence is a phenomenon which has caused so much concern in society and generated intense debates among policymakers, civil society activists and scholars. It is, therefore, no surprise that it is attracting so much scholarly attention lately. Despite the wide interest it has generated, an appropriate response grounded in law to tackle the scourge has defied logic. The situation even gets more complicated when other societal values such as marriage are present between the parties. So many (legal) mechanisms have been put in place in response to domestic violence. These responses are primarily grounded in law, mainly involving the criminal justice or legal system. Specifically, the typical response has been the use of the law and criminal justice approach. Despite the many advantages of the common approach, questions arise regarding its suitability for married partners. Indeed, recent concerns have arisen, especially in family law jurisprudence, regarding the need to preserve the institution of marriages, especially for domestic violence cases which are ‘resolvable’. This is because, in many cases, the common approach mainly results in the breakdown of marriages. Thus, the partial decriminalisation approach has begun to gain wide attention, especially in domestic violence cases between married partners. The objective of this paper is to analyse the various responses to domestic violence and their implication for the sustainability of marriages.